Gambaran Pruritus Uremik Pasien Gagal Ginjal Kronik di Unit Hemodialisa Rumah Sakit Umum Pusat Haji Adam Malik Medan - Sembiring, Friska; Nasution, Siti Saidah; Ariani, Yesi (Jurnal Perawat Indonesia, 2020)
Uremic pruritus is one of patient’s complaint about chronic kidney disease which is an uncomfortable and itchy sensation and can cause disturbances during the day or night and can even occur throughout the day such as sleep disturbance, activity, depression and complications in the skin that can reduce the quality of life of patients with chronic kidney failure. This study aims to look at the description of uremic pruritus experienced by patients with chronic kidney failure using descriptive quantitative design. The instruments used in this study were demographic data and a 5-D itch scale questionnaire. This research was conducted at the General Hospital of Haji Adam Malik Medan in one month with a sample of 49 people. The results of the study of the characteristics of respondents describe the majority of elderly (26.5%) who suffer from uremic pruritus, male gender (61.2%), have experienced uremic pruritus for more than 6 weeks (100%), the majority have undergone hemodialysis> 1 year (79.6%) and the majority are no longer working (73.5%) and hypertension is the majority of concomitant diseases (73.5%) with an itching scale of 15-24 (moderate) of 59.2%. This study provides some information on the factors that cause and that aggravate the incidence of uremic pruritus in patients with chronic renal failure so that nurses can get more leverage in nursing care for patients with uremic pruritus, especially in patients with chronic kidney failure.